(untitled) (Global Journal of Management and Business Research, 2021)
Environmental Social Responsibility (ESR) is a notion, where business integrates environmental concerns in their operations and the interaction with stakeholders, without compromising profit. To this day, ESR studies are limited to areas of ethics, society and employees while literature is blunt on its impact on societies, consumer behaviour and governments. SMEs in developing countries are not spared their approach to ESR as a sustainability strategy. SMEs’ approach seems to digress from leverage on loyalty which emanates from their nearness to communities who in turn are potential customers. This paper takes a closer look at SMEs’ approach to ESR driven by SME business owners’ perception towards ESR. The paper will take account of SMEs’ behavioural response towards ESR and establish whether they regard ESR a strategic sustainability approach with long-term positive bottom-line benefits.